Trends in Improving the Structure of a Rotary Dryer (Agricultural Engineering, 2016)
The article presents rational principles for improving the structure of a flax heap drier. As a result of tests which were carried out, we established that the counter-flow rotary dryer SKM-1 is the most perspective for drying flax heap. For effective drying of the flax heap fine fraction the second rotating screen above the loaded layer of flax heap is suggested in the SKM-1 dryer. Consequently, the drying agent processed on the bottom screen is used for preliminary drying and removal of surface moisture of the material loaded on the top screen. For the purpose of maintaining the uniform drying of the material it is recommended to carry out loosening and hashing during the drying process with the help of the loosening device, established as the V-shaped device on the discharge unit on the way to a mill. The preliminary heating of the flax heap on the top screen essentially accelerates drying and allows the increase of the dryer performance and can minimize energy requirement for drying. The correctly selected modes of the drying process provide favorable conditions for ripening flax seed, avoid damage of drying material and improve its sowing quality.